Fibroblast–immune crosstalk in oral squamous cell carcinoma: from tumor promotion to immune evasion - Liu, Xiao; Wang, Dandan; Cheng, Xue; Ma, Yining; Li, Siya; Deng, Jinhai; Qiao, Chunyan (Frontiers in Immunology, 2026)
Oral squamous cell carcinoma (OSCC) is a highly invasive malignancy marked by poor prognosis and therapeutic resistance. Within its tumor microenvironment (TME), cancer-associated fibroblasts (CAFs) and immune cells form a dynamic network that drives tumor progression. CAFs reshape the extracellular matrix, rewire tumor metabolism, and modulate immune surveillance by recruiting regulatory T cells and promoting macrophage polarization. Recent studies have highlighted CAF heterogeneity, identifying functionally distinct subtypes with differential impacts on prognosis and treatment responsiveness. CAF-derived secretomes, including cytokines, chemokines, and exosomal miRNAs, shape tumor–immune dynamics and mediate resistance to cisplatin and anti-angiogenic therapies. Crosstalk between CAFs and immune cells, particularly via the IL-6–STAT3–PD-L1 and CXCL12–CXCR4 axes, promotes immune evasion and dampens responses to checkpoint blockade. This review summarizes the phenotypic heterogeneity, metabolic functions, and secretory profiles of CAFs in OSCC, with particular emphasis on their crosstalk with immune components, highlighting the potential of CAFs-targets to enhance immunotherapy responsiveness.